Highly selective two-photon fluorescent off-on probes for imaging tyrosinase activity in living cells and tissues - Cui, Yixin; Park, Sang Jun; Wu, Xiaofeng; Wang, Rui; Qi, Sujie; Kim, Hwan Myung; Yoon, Juyoung (Chemical Communications, 2021)
A coumarin-based two-photon (TP) fluorescent off-on probe has been developed for detecting tyrosinase activity. High selectivity, sensitivity and biocompatibility enable the probes to successfully image tyrosinase activity in live cells and tissues using TP microscopy.
Keywords: High selectivity; Live cell; Living cell; Two photon; Animals; Cell Line, Tumor; Coumarins; Drug Design; Fluorescent Dyes; Humans; Limit of Detection; Mice; Microscopy, Fluorescence, Multiphoton; Monophenol Monooxygenase; Photons; Rats